Comparative Analysis of Spinal Anaesthesia and Epidural Anaesthesia for Caesarean Section: Impact on Postoperative Analgesic Consumption and Pain Management - KHALID Mutlaq Q Alanazi, Mutlaq Khalid M Alrasheedi, Naif Nafea Bin Naif Alharbi, Khalid Riyadh Kh Alanazi, Khalifah Hamed Jaser Alanazi, Sultan Fazzaa Mohammed Aldhafeeri (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Regional anesthesia is commonly used for elective caesarean sections. This study aimed to assess the impact of spinal anesthesia versus epidural anesthesia on postoperative analgesic consumption and pain relief in women undergoing elective caesarean section.Methods: A comparative analysis of spinal and epidural induction of perispinal anesthesia was conducted in 132 women (ASA I or II) scheduled for elective caesarean section, all of whom underwent epidural catheterization for perioperative anesthesia and postoperative analgesia. Patients were randomly assigned to two groups: spinal anesthesia with isobaric bupivacaine 0.5% and 5 μg sufentanil intrathecally or epidural anesthesia with ropivacaine 0.75% and 10 μg sufentanil. Postoperative analgesia was managed using patient-controlled epidural analgesia with ropivacaine 0.133% bolus (11–15 mg based on patient's height) and a lock-out time of 1 hour. Pain scores and analgesic requirements were assessed intraoperatively and for 24 hours post-surgery using visual analogue pain scales.Results: One hundred and twenty-five patients completed the study. There were no significant differences in patient-controlled epidural analgesic requirements between the spinal and epidural anesthesia groups. Intraoperative pain scores were higher with epidural anesthesia (P < 0.05). However, the overall area under the curve for pain over 24 hours was lower with spinal anesthesia (P < 0.0005). Postoperative pain scores at rest and during mobilization were consistently lower with spinal anesthesia (P < 0.05), accompanied by less motor blockade and fewer adverse effects. More patients in the epidural anesthesia group required supplemental analgesics.Conclusion: For elective caesarean sections, postoperative epidural analgesia via patient-controlled epidural analgesia is comparable between spinal and epidural anesthesia. Spinal anesthesia, however, results in less postoperative pain, reduced need for additional analgesics, and fewer side effects